An Exploration of the International Career Experiences of Argentinean Women in New Zealand - Nodesco, Luciana Ornela (Auckland University of Technology, 2019)
Self-initiated (SI) expatriates are international travellers who pursue overseas work, temporarily and by their own means (Al Ariss & Crowley-Henry, 2013; Myers, Inkson, & Pringle, 2017; Suutari, Brewster, Mäkelä, Dickmann, & Tornikoski, 2018). The experiences of this growing global workforce, and in particular the experiences of SI expatriate women, are under-researched (Ressia, Strachan, & Bailey, 2017; Van den Bergh & Du Plessis, 2012). Furthermore, little research has been carried out on Latin American women undertaking self-initiated expatriation (SIE) in New Zealand (NZ). This dissertation provides a unique contribution to the literature by exploring the motivations of Argentinean women to embark on a SIE to NZ, as well as their career experiences and development in the country. The career stories of five Argentinean SI expatriate women were analysed through narrative inquiry, which is described by Polkinghorne (1995) as a methodology that explores human experiences through storytelling. The research paradigm used is interpretive (Crotty, 1998; Grant & Giddings, 2002; Gray, 2013). The findings of this dissertation provide new insights into the strategies undertaken by the participants that contributed to their career experiences and development: mentoring, networking, access to community support, pursuing local qualifications and training. Additionally, evidence of some discriminatory practices by NZ employers was found, such as failure to recognise overseas qualifications and experience. However, SIE was a powerful experience that contributed to the participants’ career development, resulting in transformational life change for all of them. Certain implications for Argentinean women and their employers were identified. Other SI expatriate women seeking to improve their career development in NZ may find it useful to learn about the experiences, strategies and challenges which the participants shared. New Zealand employers wishing to retain or attract skilled SI expatriate women could endeavour to do so by supporting them with technical training, cross-cultural training, ongoing language training, mentoring, and formal and informal networking opportunities (Cao et al., 2013; Cao et al., 2014; Chen & Shaffer, 2017; Fontinha, De Cuyper, Williams & Scott, 2017; Howe-Walsh & Schyns, 2010; Vaiman, Haslberger, & Vance, 2015).
Keywords: Self-initiated expatriates; Argentinean; Expatriation; Career development; New Zealand; Self-initiated expatriation; Global mobility; Motivations; International experiences; International work experiences; Overseas experience; Argentinean women; Latin women; SIE